Verifying community-wide exposure to endocrine disruptors in personal care products – In quest for metabolic biomarkers of exposure via in vitro studies and wastewater-based epidemiology. (15th October 2018) - Lopardo, Luigi; Adams, David; Cummins, Andrew; Kasprzyk-Hordern, Barbara
Abstract: This study aimed to identify human specific metabolites of selected known or suspected endocrine disruptors (EDCs), mainly UV filters, used in personal care and consumer products whose metabolism has hardly been explored and to select suitable candidate biomarkers for human exposure studies using wastewater based epidemiology (WBE). The analysis of metabolic biomarkers of target chemicals is crucial in order to distinguish between internal and external exposure, since many sources contribute to chemicals being discharged into wastewater. This was achieved through the employment of a new analytical framework for verification of biomarkers of exposure to chemicals combining human biomonitoring and water fingerprinting. Eight EDCs with unknown metabolic pathways (benzophenone-1 (BP-1); benzophenone-2 (BP-2); 4, 4′-dihydroxybenzophenone (4, 4′-DHBP); 4-benzylphenol (4-BenzPh); homosalate (HO); octocrylene (OC); 3-benzylidene camphor (3-BC), and two EDCs with known metabolism (bisphenol A (BPA) and benzophenone-3 (BP-3)) were tested. The biotransformation observed consisted mainly of phase I processes such as hydrolysis and hydroxylation together with phase II conjugation reactions such as sulphation and glucuronidation. Only two chemicals (BP-1, BP-3) were identified in urine and three chemicals (BPA, BP-1, BP-3) in wastewater. Five newly discovered metabolites (HO-Met1, OC-Met1, 4-BenzPh-Met4, 4-BenzPh-Met5 and 4-BenzPh-Met6) and one previously known metabolite (BPA-Met3) were detected in tested urine/wastewater samples from five WWTPs serving large communities ranging between 17 and 100 thousand inhabitants. The presence of metabolic biotransformation products of OC, 4-BenzPh, BPA and HO in wastewater provides evidence for internal exposure of studied populations to these chemicals. Graphical abstract: Image 1 Highlights: Wastewater fingerprinting was applied to verify public exposure to endocrine disruptors. Five new metabolites of octocrylene, homosalate and 2-benzylphenol were identified using in-vitro assays. Two hydrolytic metabolites of octocrylene and homosalate were identified in wastewater. 4-benzylphenol resulted in the formation of sulphated and hydroxylated metabolites.